A participação do Movimento Estudantil na política de formação profissional em serviço social no Brasil nos anos 1990 - Silva, Vilma Jara da (2025)
This dissertation analyzes the participation of the Social Work Student Movement (MESS) in professional training policy in Brazil during the 1990s, highlighting its role in the internal democratization of the Brazilian Association of Teaching and Research in Social Work (ABEPSS) — formerly the Brazilian Association of Schools of Social Work (ABESS) — and in the formulation of the 1996 Curriculum Guidelines. The research starts from the following problem: what processes were decisive for the political participation of Social Work students in the professional training policy coordinated by ABESS/ABEPSS in the 1990s? The general objective is to historically analyze this participation, articulating it with the ethical-political project of the profession. The specific objectives involve uncovering the student confrontations and agendas of the 1980s and 1990s; investigating the trajectory of the MESS and its relationship with ABESS/ABEPSS; and examining student action in the process of curricular revision and approval of the 1996 Curriculum Guidelines. and to analyze student representation within the organization's structure. The historical-dialectical materialism method is adopted, combining bibliographic research, document analysis, and semi-structured interviews with new activists who were active in the MESS in the 1990s and later joined the administrations of ABEPSS and/or the Federal Council of Social Work (CFESS). The analysis reveals that the MESS, heir to a tradition of resistance within the Brazilian student movement, consolidated itself as an independent political subject, articulating general agendas—such as the defense of public, free, secular, and high-quality universities—with specific demands of the profession, such as curricular reform and the democratization of ABEPSS's decision-making bodies. It is evident that the 1990s, marked by the neoliberal offensive and productive restructuring, constituted a decisive moment of political tension and collective formulation in Social Work, in which student protagonism was crucial for the consolidation of a critical and socially referenced training policy, particularly in the debate on the Curricular Guidelines. By recording this trajectory, the study contributes to the political memory of the profession and reaffirms the importance of student activism as a formative and influential space, capable of connecting academic training to broader social struggles.